ANALISIS KESEHATAN BUMDES BERDASARKAN ASPEK PERMODALAN, LIKUIDITAS, KEMANDIRIAN DAN PERTUMBUHAN PADA BUMDES USAHA SEJAHTERA DESA KARANGSONO, KECAMATAN BANGSALSARI - Oktaviani, Nadia; Sari, Maheni Ika; Hermawan, Haris (Relawan Jurnal Indonesia, 2022)
This study aims to determine and analyze the health of BUMDes based on aspects of capital, liquidity, independence and growth (case study of BUMDes Usaha Sejahtera, Karangsono Village, Bangsalsari District, Jember Regency). The type of research used is quantitative research. This study uses external secondary data sources obtained through literature studies which are arranged in the form of documents in the form of reports, books and other written sources related to the object of research and primary data sources, namely financial report data in the form of Balance Sheet reports and Profit and Loss reports for BUMDes Business. Prosperous period 2018-2020. The analytical tool used in this research is the analysis of liquidity ratios, solvency ratios, activity ratios, and profitability ratios. The results of this study indicate that the health of BUMDes based on aspects of capital, liquidity, independence and growth in terms of liquidity ratios, solvency ratios, activity ratios and profitability ratios is quite healthy. The factors that affect the soundness of BUMDes Usaha Sejahtera in 2018-2020 are having a high liquidity ratio to pay obligations that are soon due by using assets or assets owned by the company, successfully reducing asset financing by debt and fully using own capital in operational activities. company, is able to manage receivables with a fast receivables turnover ratio so that it is profitable for BUMDes Usaha Sejahtera, and is able to maintain the company's profit level and even increase the profit percentage